Mathematical modeling and simulations of vibrations from a spur gearbox - Yeo, Cun Lai. (2013)
In this report, the dynamic behavior of a single stage spur gear transmission is studied. Time varying stiffness is an internal excitation which is hard to control due to the changing combined torsional stiffness. The reason for the change of the combined torsional stiffness is due to the type of contact in the line of action. Dynamic response was studied to see the effect the time varying stiffness.